Integrasi Nilai-Nilai Islam dalam Asuhan Kebidanan pada Ibu Hamil dan Bersalin - Ahlun Nazi Siregar; Ica Delfiza; Julian Wulan Sari; Sesvira Audisha; Metha Novria Dipa; Triadna Levisa; Ridya Ambar Julika; Dinda Rahayu Amalia; Rina Gunawan (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
This study aims to explore the integration of Islamic values into midwifery care for pregnant and birthing mothers, with a focus on applying spiritual principles in healthcare practices. Using an exploratory qualitative approach through in-depth interviews with Muslim midwives and literature review, the study finds that the implementation of Islamic values—such as maintaining modesty (aurat), observing proper manners in interactions, and providing spiritual support through prayer and remembrance (dhikr)—is consistently practiced in midwifery care. The integration of these values has been shown to enhance comfort, psychological calmness, and mental preparedness of mothers during pregnancy and childbirth. Furthermore, midwives act as spiritual facilitators who not only provide medical care but also build emotional connections and trust with patients. However, challenges remain in implementing Islamic value integration, including a lack of formal training, limited practical guidelines, and institutional barriers. The findings highlight the importance of developing curricula, training programs, and national guidelines to strengthen midwifery care practices based on Islamic values, aiming to achieve holistic, humanistic, and culturally rooted healthcare services.